A study of training motivation as a mediator on the relationship between training framing and training effectiveness - Dayangku Zyzy Cemyly, Binti Awang Rahmat. (2009)
This study aimed to identify the mediating role of training motivation in the relationship between training framing and training effectiveness components i.e. utility reactions, transfer motivation and also learning. The findings of the study could provide awareness and guidelines for organization of the importance of training framing in increasing employees’ motivation and further increasing the training effectiveness.